Education through the Approach to Using Regional Languages on the Level of Community Understanding Related to the Covid-19 Vaccine in Tabumela Village, Tilango District Gorontalo - Fadly Syamsuddin; Abdul Wahab Pakaya; Delfiyana; Riyan Kodai; Rosmawati Thalib; Tarsiyah (Pusat Studi Pembangunan dan Pemberdayaan, 2021)
Language is the most prominent distinguishing feature because with language each social group feels itself as a different unit from other groups, where society is a group of people who live together in an area and then form a system. COVID-19 is a disease caused by (SARS-CoV2), which can cause symptoms such as fever, headache, muscle aches, impaired smell, decreased taste, sore throat, respiratory problems, nausea/vomiting/abdominal pain, other symptoms according to organs. Thus, what we have to do to prevent the spread can be done by giving vaccines. COVID-19 vaccination is an important part of efforts to handle the COVID-19 pandemic which is comprehensive and integrated, covering aspects of prevention by implementing health protocols: keeping distance, washing hands with soap and wearing masks (3M), COVID-19 vaccination, and 3T (Test, Search, Follow up). Based on the results of the training, it showed that most of the people stated that this education was very useful because they gained knowledge and understanding regarding the covid-19 vaccine in using the local language